Inibição da mineralização de compostos nitrogenados de lixiviado de macrófita aquática: Adequação metodológica - Nunes, Maíra de Figueiredo [UNESP] (2008)
This study aimed to establish the adequate concentrations of nitrapyrin for the effective inhibition of oxygen demand required for the oxidation of nitrogen compounds during aerobic mineralization of leachate. The aquatic macrophyte Myriophyllum aquaticum was used as a source of dissolved organic matter (DOM). The leachate was incubated in several chambers, containing different composition and treatments: (i) treatment with leachate (DOM), (ii) treatment with DOM plus nitrapyrin in different concentrations (10; 25 and 50 mg L-1), aiming at finding the right concentration that inhibits the nitrification process, (iii) treatment with DOM plus NH4SO 2, (iv) treatment containing DOM and nitrapyrin plus NH 4SO2, and (v) treatment with DOM plus azide. The dissolved oxygen amount in each incubation treatment was periodically measured. The results indicated that the ratio of 10 mg L-1 of nitrapyrin for each 10 mg C of leachate is efficient in inhibiting the oxidation of nitrogen compounds from aquatic macrophytes.